2021
DOI: 10.21273/hortsci15452-20
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Response of In Vitro Cannabis sativa Plants

Abstract: The majority of commercial Cannabis sativa L. (cannabis) cultivators use a 12.0-hour uninterrupted dark period to induce flowering; however, scientific information to prove this is the optimal dark period for all genotypes is lacking. Knowing genotype-specific photoperiods may help to promote growth by providing the optimal photoperiod for photosynthesis. To determine whether the floral initiation of cannabis explants respond to varied photoperiods in vitro, explants were grown under one of six photoperiod tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Generally, many compounds require differentiated tissues for efficient production. Moher et al [ 59 ] demonstrated that in vitro plants respond to photoperiod and that they develop “normal” looking flowers. While the cannabinoid content of these flowers has not been examined, it is likely that they produce much higher levels than would be observed in undifferentiated tissues, or roots.…”
Section: In Vitro Culture In Cannabismentioning
confidence: 99%
“…Generally, many compounds require differentiated tissues for efficient production. Moher et al [ 59 ] demonstrated that in vitro plants respond to photoperiod and that they develop “normal” looking flowers. While the cannabinoid content of these flowers has not been examined, it is likely that they produce much higher levels than would be observed in undifferentiated tissues, or roots.…”
Section: In Vitro Culture In Cannabismentioning
confidence: 99%
“…Since many nations have adopted the more liberal view of cannabis, it’s since gained higher economic status as an industrial crop, and additional secondary products such as extract derivatives are expected to further amplify economic expansion ( Moher et al, 2020 ). The need to maintain product consistency, while supporting innovation and development ( Burgel et al, 2020 ) requires a better understanding of the physiological responses of cannabis to external stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…A day length of 12 and 18 h are common practices to induce flowering or keep plants vegetative, respectively (Potter, 2014 ). Moher et al ( 2020 ) indicated that C. sativa “802,” although not categorized as hemp given its 15–20% THC content, had a critical photoperiod between 15 and 16 h. Growth chamber environments are ideal for investigating the photoperiodism of hemp. With artificial lighting (typically from light-emitting diodes) being the only radiation source indoors, the photoperiod is strictly controlled by the hours of light operation.…”
Section: Introductionmentioning
confidence: 99%